Assessment of arsenic and selenium in cyprinus carpio from alaro stream in Ibadan, Nigeria (2014)
An assessment was carried out on the concentration of arsenic (As) and selenium (Se) in the organs of Cyprinus carpio from Alaro stream in Ibadan, Nigeria. A total of 32 fish were collected from the sampling of Alaro stream from June to December 2003 and preserved by freezing. Dissections were carried out using dissecting set in order to remove the gills, fins, gut (intestine), liver, bones and muscle. Acid digestion was carried out after drying and pulverization of the fish organs. Inductively coupled plasma-mass spectrometer (ICP-MS) was used for the trace metal analyses while bovine liver standard reference material (SRM) from the National Institute of Standards (NIST) was used for quality assurance of the results. The range of the As in the organs of C.carpio was 0.000- 0.963ppm, while the following increasing order of mean concentration: fins<liver<gills< muscle < gut< bone was observed. The range of Se in the organs was 0.06-11.80ppm with an increasing order of mean concentration of: bone<gut<fins <muscle <gills<liver. This study also shows that mean concentration of As and Se in the organs C.carpio collected from the Alaro stream in Ibadan exceeded the World Health Organization (WHO) guideline limits set the trace metals in food. This shows that Alaro stream is polluted and fish such as C.carpio caught from the stream is unhealthy for human consumption due to the public health consequences posed in consuming such contaminated food.